2017
DOI: 10.1007/s00268-017-4040-5
|View full text |Cite|
|
Sign up to set email alerts
|

Paraesophageal Hernia and Reflux Prevention: Is One Fundoplication Better than the Other?

Abstract: The argument of whether or not a fundoplication should be added to a PEH repair in patients without evidence of reflux still persists. However, this review highlights that, when a fundoplication is performed, a tailored approach based on preoperative function tests is almost always preferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…15.7% radiological 0 57.5 4.4% conversions 7.8% morbidity Daigle et al [68] 2015 101 101 SC = 94 16.8% endoscopic/ radiological 0 10.9 22% morbidity 29.7% reflux Yates et al [69] 2015 11 HR 10 TG = 11 0% symptomatic N/A 3 2 readmissions 2 TG dislocations Higashi et al [70] 2017 To date, there is no consensus on the type of wrap and on the fixation of the fundoplication to the esophagus or the diaphragmatic pillars [28] . In a systematic review of the literature, including 24 studies, Andolfi et al [77] concluded that the preferred approach should be a total fundoplication when the esophageal motility is normal.…”
Section: Gastroesophageal Refluxmentioning
confidence: 99%
“…15.7% radiological 0 57.5 4.4% conversions 7.8% morbidity Daigle et al [68] 2015 101 101 SC = 94 16.8% endoscopic/ radiological 0 10.9 22% morbidity 29.7% reflux Yates et al [69] 2015 11 HR 10 TG = 11 0% symptomatic N/A 3 2 readmissions 2 TG dislocations Higashi et al [70] 2017 To date, there is no consensus on the type of wrap and on the fixation of the fundoplication to the esophagus or the diaphragmatic pillars [28] . In a systematic review of the literature, including 24 studies, Andolfi et al [77] concluded that the preferred approach should be a total fundoplication when the esophageal motility is normal.…”
Section: Gastroesophageal Refluxmentioning
confidence: 99%
“…However, the disruption of the crural diaphragm during dissection of the gastroesophageal junction and the resulting risk of developing de-novo esophagitis may represent a strong rationale favoring routine fundoplication (37). Whether one fundoplication may be more suitable than another according to symptoms and objective findings on preoperative assessment has been investigated in a recent review by Andolfi et al (38). Unfortunately, the authors reported a paucity of highquality evidence in favor of a certain type of fundoplication over another in avoiding reflux and dysphagia following PEH repair.…”
Section: Gerdmentioning
confidence: 99%
“…Fundoplication, the wrap of the gastric fundus around the distal part of the esophagus, was introduced by Nissen[1] in 1956, as a surgical treatment of gastroesophageal reflux disease (GERD), and is currently considered as the operation of choice, when conservative approaches fail[2]. Since the extent of the plication was correlated with postoperative functional complications, various modifications ( e.g ., Hill, Toupet) of the original technique have been described[3-5]. Besides these, fundoplication has been, also, an important restoration element in other procedures, such as, Heller myotomy for esophageal achalasia[6].…”
Section: Introductionmentioning
confidence: 99%